2021
DOI: 10.1007/s12665-021-09952-5
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study on characteristics of impact compression of freeze–thawed granite samples under four different states considering moisture content and temperature difference

Abstract: The mechanics of rock masses in cold regions have attracted the attention of researchers from all over the world, and the concern here is that the mechanical properties of rock masses are inevitably weakened under freeze-thaw cycles. In this paper, firstly, granite samples were subjected to different freeze-thaw cycles, after that, we dealt with the freeze-thawed samples considering four different states, such as saturated and frozen states, saturated and normal temperature states, dry and frozen states as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Some scholars have conducted impact compression experiments on granite specimens with different water contents and degrees of freezing using separated Hopkinson rods. The effect of water on the dynamic modulus of elasticity was more significant than the effect of freeze-thaw temperature [22]. Some scholars also investigated the shear strength of specimens with different water contents after freezing and thawing using fine-grained sand from the drainage field and found that the samples' shear strength decreased the most after a single freeze-thaw action, and the specimens' cohesion and internal friction angles decreased according to water content with the increasing numbers of freeze-thaw cycles.…”
Section: Introductionmentioning
confidence: 90%
“…Some scholars have conducted impact compression experiments on granite specimens with different water contents and degrees of freezing using separated Hopkinson rods. The effect of water on the dynamic modulus of elasticity was more significant than the effect of freeze-thaw temperature [22]. Some scholars also investigated the shear strength of specimens with different water contents after freezing and thawing using fine-grained sand from the drainage field and found that the samples' shear strength decreased the most after a single freeze-thaw action, and the specimens' cohesion and internal friction angles decreased according to water content with the increasing numbers of freeze-thaw cycles.…”
Section: Introductionmentioning
confidence: 90%
“…Weakly consolidated rocks, such as mudstone, claystone, and expansive softrock, in water-rich regions, are susceptible to structural degradation due to F-T cycles in seasonally frozen environments. Extensive experimental studies, which include unconfined compressive tests [13], triaxial shear tests [14], Brazilian tensile tests [15], point loading tests [16], and split Hopkinson pressure bar tests [17] on weakly consolidated rocks, have consistently demonstrated a noteworthy decline in its mechanical properties with an increasing number of F-T cycles. Hong et al (2021) proposed a predictive model for uniaxial compressive strength of expansive soft rock that integrates F-T cycles, based on the elastic-plastic theory, and fatigue damage mechanics [18].…”
Section: Introductionmentioning
confidence: 99%
“…Rock is a material ubiquitous in mines, expressways, tunnels, dams, slopes, and other rock mass engineering [ 1 , 2 , 3 ], as shown in Figure 1 . The construction and operation of engineering are closely related to the physical and mechanical properties of rocks [ 4 , 5 , 6 ], whereas rock is essentially a kind of heterogeneous medium, which is a complex mineral aggregate formed under physical and chemical actions after a long geological process [ 7 , 8 ]. It is mainly composed of a variety of mineral grains and cements and contains a large number of defects, such as joints, micro-cracks, pores, holes, and faults [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%